Antifungal properties and inhibitory effects upon aflatoxin production by Zingiber officinale essential oil in Aspergillus flavus. (30th October 2015) - Nerilo, Samuel B.; Rocha, Gustavo Henrique O.; Tomoike, Caroline; Mossini, Simone A. G.; Grespan, Renata; Mikcha, Jane M. G.; Machinski, Miguel
Summary: In this study, the efficacy of g inger ( Zingiber officinale Roscoe) essential oil (GEO) in reducing A. flavus growth and aflatoxin production was investigated. Gas chromatography coupled to mass spectrometry and nuclear magnetic resonance spectroscopy showed that the major components of GEO were α‐zingiberene (23.85%) and geranial (14.16%). Mycelial growth of Aspergillus flavus was reduced significantly at a GEO concentration of 150 μg mL −1, and complete inhibition of conidial germination was observed at a concentration of 10 μg mL −1 . Statistically significant inhibition of ergosterol biosynthesis was detected at a GEO concentration of 10 μg mL −1 . GEO was capable of fully inhibiting aflatoxin production by A. flavus at a concentration of 15 μg mL −1 . The results suggest that low concentrations of GEO are capable of inhibiting aflatoxin production; such ability could be valuable in the upcoming future for agricultural companies to better control aflatoxigenic fungi in agricultural products. Abstract : (A): Control (mycelia of untreated); (B) Mycelia with essential oil at 5 μg mL −1 ; (C) Mycelia with essential oil at 10 μg mL −1 ; (D) Mycelia with essential oil at 15 μg mL −1 ; (E) Mycelia with essential oil at 20 μg mL −1 ; (F) Mycelia with essential oil at 25 μg mL −1 .